Company Growth, Profitability, and Capital Structure in Food and Beverage Firms: Pertumbuhan Perusahaan, Profitabilitas, dan Struktur Modal di Perusahaan Makanan dan Minuman - Fafarita , Alliansi Wulan; Nirwana, Nihlatul Qudus Sukma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Capital structure decisions play a crucial role in maintaining corporate financial stability. Specific Background: Food and beverage companies face dynamic funding needs due to operational expansion and market competition. Knowledge Gap: Empirical evidence on how company growth and profitability relate to capital structure in this sector remains limited for the 2019–2023 period. Aims: This study investigates the relationship between company growth, profitability, and capital structure. Results: Using multiple linear regression on 19 food and beverage companies listed on the Indonesia Stock Exchange, the findings indicate that both company growth and profitability are significantly associated with capital structure. Novelty: This study provides updated empirical evidence using recent financial data in the Indonesian food and beverage sector. Implications: The results offer practical insights for corporate managers in formulating financing strategies based on firm growth and profitability performance. 11545 Other,+Report_JURNAL+Alli… Highlight & Keyword (Bold, English) Highlights: Company growth is associated with capital structure Profitability shows a significant relationship with leverage Food and beverage sector financing characteristics Keywords: Company Growth, Profitability, Capital Structure, Food and Beverage Firms, Financial Structure